Citizen and political party – Introduction to the analysis of the Platforma Obywatelska and Prawo i Sprawiedliwość - Plecka, Danuta (Political Preferences, 2017)
The problem of both political and sociological backgrounds is often the quality and level of political civic competence. They point out their importance for the development and consolidation of democracy as well as the quality of public life. Research on this topic is accompanied by a lack of interest in politics, knowledge of its basic mechanisms, limited social trust, and marginal participation, which may be the turnout in individual elections. At the same time, there is a lack of reflection on the sources of such behaviors, assuming (usually a priori) that they are in the historical experience, mentality, tradition or political culture prevailing in a given society. However, the observation of public life makes it possible to argue that the quality and level of political civic competences largely depend on the practice of political parties with regard to citizens in terms of both conventional and unconventional participation. Of course, it is difficult not to notice the interplay of political parties and citizens, one can even risk the notion that the "quality of citizenship" depends on the rulers, and these reflect the "quality of citizenship." Key words: civil society, political civic competence, political party, democracy